2020
DOI: 10.5194/acp-2020-809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of morphology, mobility size and SOA material coating on the ice nucleation activity of black carbon in the cirrus regime

Abstract: Abstract. There is evidence that black carbon (BC) particles may affect cirrus formation and hence global climate by acting as potential ice nucleating particles (INPs) in the troposphere. Nevertheless, the ice nucleation (IN) ability of bare BC and BC coated with secondary organic aerosol (SOA) material remains uncertain. We have systematically examined the IN ability of 100–400 nm size-selected BC particles with different morphologies and different SOA coatings representative of anthropogenic (toluene and n-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 123 publications
(217 reference statements)
1
2
0
Order By: Relevance
“…Mahrt et al (2020b), who found the ice nucleation ability of processed, compacted soot particles to be significantly higher compared to unprocessed, more fractal soot. This is further supported by recent result of Zhang et al (2020), who investigated different laboratory analogues of soot and found the largest ice nucleation activity to be associated with the most spherical, i.e. compacted soot type.…”
Section: Atmospheric Implicationssupporting
confidence: 77%
See 2 more Smart Citations
“…Mahrt et al (2020b), who found the ice nucleation ability of processed, compacted soot particles to be significantly higher compared to unprocessed, more fractal soot. This is further supported by recent result of Zhang et al (2020), who investigated different laboratory analogues of soot and found the largest ice nucleation activity to be associated with the most spherical, i.e. compacted soot type.…”
Section: Atmospheric Implicationssupporting
confidence: 77%
“…Soot-PCF requires pore space available for water to condense. Hydrophobic coatings can fill the pores and make them unavailable for PCF, as has been demonstrated recently for soot coated with different types of secondary organic material (Zhang et al, 2020). Similarly, ice nucleation by soot generated from propane flames was found to shift to higher ice supersaturation and eventually vanish with increasing organic carbon content (Crawford et al, 2011;Mahrt et al, 2018;Möhler et al, 2005b).…”
Section: Atmospheric Implicationsmentioning
confidence: 52%
See 1 more Smart Citation